Peran SDM Dalam Mencapai Keunggulan Kompetitif - Aprinawati Aprinawati; Evi Maria Marsaulina Br Hutabarat; Ibnu Hafizh Hasibuan; Lisa Mutia Sari; Sinar Lovelya Serawani Lumbantobing (Jurnal Riset Ekonomi dan Akuntansi, 2024)
MDSM plays a role in selecting and maintaining the best abilities. Competitive advantage will be gained by businesses that are able to attract, develop and retain high potential employees. Human Resources is responsible for finding people who have the necessary information and values that match the organization's vision and mission. According to Malayu Hasibuan (2013) MDSM is knowledge and expertise related to the relationships and work of the workforce so that they are feasible and effective in helping to understand the goals of associations, workers and society through the resolution of human assets. the executives work like preparations. sorting, acquisition, improvement, remuneration, coordination, support, discipline, and ending. Viable advantage is characterized as a state in which the competitive cannot imitate the positive side of the organization that enjoys great advantages and prevents it from competing or competing (Macky and Johnson, 2003).